2012
DOI: 10.1016/j.foreco.2012.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ungulate herbivory on aspen, cottonwood, and willow development under forest fuels treatment regimes

Abstract: a b s t r a c tHerbivory by domestic and wild ungulates can dramatically affect vegetation structure, composition and dynamics in nearly every terrestrial ecosystem of the world. These effects are of particular concern in forests of western North America, where intensive herbivory by native and domestic ungulates has the potential to substantially reduce or eliminate deciduous, highly palatable species of aspen (Populus tremuloides), cottonwood (Populus trichocarpa), and willow (Salix spp.). In turn, different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
(49 reference statements)
1
21
0
1
Order By: Relevance
“…Our results are consistent with numerous other studies that have shown differences in composition but not diversity of woody plant communities when experiencing elk and other ungulate browse pressure (Ammer, 1996;Hobbs, 1996;Moser and Witmer, 2000;Peinetti et al, 2001;Rooney and Waller, 2003;Sankaran et al, 2008; but see Johnson and Cushman, 2007;Beschta and Ripple, 2008). Elk foraging is also known to reduce tree sapling and seedling density, biomass, and regeneration (McPherson, 1993;Scheiner et al, 1995;Baker et al, 1997;Zeigenfuss et al, 2002;Endress et al, 2012) and shrub biomass and regeneration (Scheiner et al, 1995;Singer and Renkin, 1995;Huffman and Moore, 2003;Johnson and Cushman, 2007). White-tailed deer appear to affect woody plant communities similarly (Rooney and Waller, 2003).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with numerous other studies that have shown differences in composition but not diversity of woody plant communities when experiencing elk and other ungulate browse pressure (Ammer, 1996;Hobbs, 1996;Moser and Witmer, 2000;Peinetti et al, 2001;Rooney and Waller, 2003;Sankaran et al, 2008; but see Johnson and Cushman, 2007;Beschta and Ripple, 2008). Elk foraging is also known to reduce tree sapling and seedling density, biomass, and regeneration (McPherson, 1993;Scheiner et al, 1995;Baker et al, 1997;Zeigenfuss et al, 2002;Endress et al, 2012) and shrub biomass and regeneration (Scheiner et al, 1995;Singer and Renkin, 1995;Huffman and Moore, 2003;Johnson and Cushman, 2007). White-tailed deer appear to affect woody plant communities similarly (Rooney and Waller, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Western elk populations can significantly alter plant community composition and reduce biodiversity, including the loss of shrub species richness (Johnson and Cushman, 2007), reduction of tree and shrub mass and frequency (Schreiner et al, 1995;Riggs et al, 2000;Endress et al, 2012), and reduction in tree seedling numbers and sapling growth (Kuiters and Slim, 2002;Schoenecker et al, 2004). Woody browse is a major component of elk diet and is often negatively affected by elk foraging (reviewed in Toweill et al, 2002;Huffman and Moore, 2003;Johnson and Cushman, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The positive influences of disturbance such as wildfire or logging on developing diverse and productive plant communities may be countered by chronic herbivory because these community types are often highly attractive foraging areas (Wisdom et al , Endress et al ). A classical perception is that reducing densities of herbivores may help bolster per capita nutrition, nutritional condition, and productivity (Fowler , McCullough ).…”
Section: Management Implicationsmentioning
confidence: 99%
“…2002, Beschta 2005. The conspicuous alleviation of one factor, elk herbivory, during the past few years may not be a strong basis for concluding that it is the primary cause of a sea change in aspen demography, as studies have further suggested that aspen do not always respond to experimental protection from herbivory (Endress et al 2012). To date, however, there is an absence of research capable of isolating the effect of elk herbivory from other factors that may influence aspen, including temperature (Brown et al 2006), moisture (Romme et al 1995), snow pack (Brodie et al 2012), bovid herbivory (Kimble et al 2011, and competition with conifers (Bartos 2001).…”
Section: Aspenmentioning
confidence: 99%